2021
DOI: 10.1155/2021/9003603
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Re Improves Inflammation and Fibrosis in Hepatic Tissue by Upregulating PPARγ Expression and Inhibiting Oxidative Stress in db/db Mice

Abstract: Ginsenoside Re (Re) is the main component of “Zhenyuan Capsule” (ZYC), which was wildly used in clinic in China for adjunctive treatment of coronary heart disease (CHD) and type II diabetes (T2DM). Nonalcoholic fatty liver disease (NAFLD) is one of the most important complications of T2DM, as well as an important risk factor of CHD. The aim of the present study was to investigate the effects of Re on NAFLD in db/db mice, one of the most recognized gene deficient animal models on T2DM. Sixteen db/db mice and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 29 publications
4
23
0
1
Order By: Relevance
“…Although the underlying mechanisms could not be delineated by this study, included articles have suggested several protective mechanisms mediated by Panax ginseng treatment against NAFLD. First, in hepatocytes, Panax ginseng treatment suppressed NAFLD-induced cellular stress responses, such as oxidative stress [ 23 , 50 ], ER stress [ 35 , 47 ], and mitochondrial dysfunction [ 26 ]. In addition, the administration of Panax ginseng has beneficial effects on hepatic energy metabolism by activating AMP-activated protein kinase [ 22 , 29 , 56 , 58 ] but inhibiting the mammalian target of rapamycin complex 1 [ 37 ], resulting in the normalization of hepatic glucose [ 30 ] and lipid metabolism [ 32 , 33 , 34 , 41 ] in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the underlying mechanisms could not be delineated by this study, included articles have suggested several protective mechanisms mediated by Panax ginseng treatment against NAFLD. First, in hepatocytes, Panax ginseng treatment suppressed NAFLD-induced cellular stress responses, such as oxidative stress [ 23 , 50 ], ER stress [ 35 , 47 ], and mitochondrial dysfunction [ 26 ]. In addition, the administration of Panax ginseng has beneficial effects on hepatic energy metabolism by activating AMP-activated protein kinase [ 22 , 29 , 56 , 58 ] but inhibiting the mammalian target of rapamycin complex 1 [ 37 ], resulting in the normalization of hepatic glucose [ 30 ] and lipid metabolism [ 32 , 33 , 34 , 41 ] in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…( A ) A graph of the risk in the bias of included studies. ( B ) A summary of the risk of bias in the included studies [ 7 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations